Transgenetic algorithm for the periodic mobile piston pump unit routing problem with continuous oil replenishment. (10th November 2010) - Goldbarg, Marco Cesar; Goldbarg, Elizabeth Ferreira Gouvea; Duarte, Herbert De Melo
This paper reports the application of a transgenetic algorithm to the periodic mobile piston pump unit routing problem with continuous oil replenishment, a complex problem that occurs in the exploitation of onshore oil fields. The transgenetic algorithms are inspired on the endosymbiosis and on mechanisms of genetic exchange that exist in the intracellular flow. A computational experiment is reported to validate the performance of the proposed approach. In view of the difficulty in obtaining exact solutions to the problem, an upper limit is proposed. Aiming to bring the cases tackled in the computational experiment to operating conditions of onshore fields, a set of instances is built under realistic conditions of work.